Protic Ionic Liquids‐Based Crosslinked Polymer Electrolytes: A New Class of Solid Electrolytes for Energy Storage Devices. Issue 11 (5th November 2020) - Stettner, Timo; Lingua, Gabriele; Falco, Marisa; Balducci, Andrea; Gerbaldi, Claudio
Abstract : Protic ionic liquid–based crosslinked polymer electrolytes may enable next generation low‐cost, all‐solid‐state Li‐metal batteries and electric double layer capacitors providing high energy/power density to be used in safe traction energy storage systems operating in a broad temperature range. More details can be found in article number 2000742 by Andrea Balducci, Claudio Gerbaldi, and co‐workers.